Development of competences as an integration process that is alternating in the learning venue - current considerations - Pittich, Daniel [Verfasser]; Tenberg, Ralf [Verfasser] (My University, 2013)
"This paper attempts to give an introduction of German and international theoretical starting points, findings and especially of questions in the context of a divided occupational learning. The studies of the German-speaking area can be summarized under the term of 'Lernortkooperation'. A glance in the international literature shows, that an integrative professional learning is not a genuine aspect of the German dual system in VET and exists in similar form in other vocational training systems. The studies/approaches of Gulie & Griffiths (2001, 2003) and Tynjälä (2009) on 'Connectivity' and 'Transformation' seem to be an interesting starting point, because they take both, organizational and didactic perspectives of integrative mediation and of professional competence into account." (Autorenreferat, BIBB-Doku)

"Im Beitrag wird das Problem einer Verknüpfung von theoretischen und praktischen Lernprozessen an unterschiedlichen Lernorten im deutschen dualen System der Berufsausbildung aufgegriffen. Es ist festzustellen, dass sich die deutschsprachigen Studien größtenteils auf organisatorische Aspekte (Konzept der Lernortkooperation) beziehen, didaktische Aspekte sind unterrepräsentiert. Ein Blick in die internationale Literatur zeigt, dass die Lernortteilung kein genuiner Aspekt des deutschen Dualen Systems ist, sondern in unterschiedlichen Ausprägungen auch in anderen Berufsbildungssystemen existiert. Die Ansätze von Guile & Griffiths (2001, 2003) und Tynjälä (2009) zu 'Connectivity' und 'Transformation' zeigen sich als ein interessanter Ausgangspunkt weiterführender Forschung, da dort sowohl organisatorische, als auch didaktische Perspektiven für eine integrative berufliche Kompetenzvermittlung aufgearbeitet werden." (Autorenreferat, BIBB-Doku)
Kompetenzentwicklung als lernortalternierender Integrationsprozess - aktuelle Überlegungen
Keywords: S 1.3.1 Ausbildung im Dualen System; S 2.4.1 Lernortkooperation; L 2.2 Didaktik; Duales System; Lernortkooperation; Kompetenzerwerb; Kompetenzentwicklung; Theorie-Praxis; Didaktik